A Democratic Dilemma of European Power to Tax: Reconstructing the Symbiosis Between Taxation and Democracy Beyond the State? - Jussi Jaakkola (Cambridge University Press, 2022)
In Western capitalist societies, the three postwar decades witnessed a strong interconnection between income taxation and democracy. On the one hand, the democratically representative political process constituted a precondition for the legitimacy of taxation. On the other hand, redistributive income taxation enhanced conditions for equal democratic participation by allocating resources and equalizing political power among citizens. The asymmetric European integration that has advanced transnationalization of cross-border market order but preserved income taxation under national political authority has established fiscal interdependence between Member States of the EU and exposed them to transnational regulatory effects. As a result, Member States’ performance to uphold the symbiosis between democracy and taxation has eroded. While this has led some to call for further integration of taxes beyond the nation state, others have remained skeptical about the democratic legitimacy of Europeanized taxation. This Article argues that the Europeanization of income taxation would help to reconstruct the conditions under which the symbiosis between income taxation and democracy is restored, although this requires the notion of democratic community to be reinterpreted according to the standards that cannot be equated with nation-based boundaries of a political community.